2020
DOI: 10.1155/2020/9316751
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan Ameliorates Oxidative Stress, Inflammation, DNA Damage, and Hepatorenal Injuries in Diabetic Rats Intoxicated with Aflatoxin B1

Abstract: The current study was carried out to evaluate the ameliorative effect of fucoidan against aflatoxicosis-induced hepatorenal toxicity in streptozotocin-induced diabetic rats. Sixty-four Wister albino male rats were randomly assigned into eight groups (8 rats each) that received normal saline, fucoidan (FUC) at 100 mg/kg/day orally for 4 weeks, streptozotocin (STZ) at 50 mg/kg/i.p. single dose, STZ plus FUC, aflatoxin B 1 (AFB 1 ) at 50 μg/kg/i.p. after one month of the beginning of the experiment for 2 weeks, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 60 publications
6
35
1
Order By: Relevance
“…Aleissa et al [ 9 ] registered elevated levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in a model of streptozotocin-induced diabetes mellitus in rats. Fucoidan isolated from Saccharina japonica diminished the toxic effects of diabetes and/or aflatoxin B1 on the liver and kidneys via reducing the blood glucose levels and serum levels of IL-1β, IL-6, and TNF-α [ 9 ].…”
Section: Anti-inflammatory Activity Of Fucoidan: Evidence From In mentioning
confidence: 99%
See 3 more Smart Citations
“…Aleissa et al [ 9 ] registered elevated levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in a model of streptozotocin-induced diabetes mellitus in rats. Fucoidan isolated from Saccharina japonica diminished the toxic effects of diabetes and/or aflatoxin B1 on the liver and kidneys via reducing the blood glucose levels and serum levels of IL-1β, IL-6, and TNF-α [ 9 ].…”
Section: Anti-inflammatory Activity Of Fucoidan: Evidence From In mentioning
confidence: 99%
“…Aleissa et al [ 9 ] registered elevated levels of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) in a model of streptozotocin-induced diabetes mellitus in rats. Fucoidan isolated from Saccharina japonica diminished the toxic effects of diabetes and/or aflatoxin B1 on the liver and kidneys via reducing the blood glucose levels and serum levels of IL-1β, IL-6, and TNF-α [ 9 ]. Xu et al [ 56 ] performed a similar research, however, they reported decreased kidney levels of IL-6 and no change in the TNF-α levels after treatment with LMWF from the same brown alga.…”
Section: Anti-inflammatory Activity Of Fucoidan: Evidence From In mentioning
confidence: 99%
See 2 more Smart Citations
“…Fisetin can enhance various antioxidant enzymes, attenuate the oxidative stress-inflammatory pathway induced by AFB 1 , and reduce the risk of liver cancer [63]. Fucoidan relieves liver and kidney damage caused by AFB 1 by reducing oxidative stress, DNA damage, and inflammation [64].…”
Section: Exogenous Substances Alleviate the Toxicity Of Afbmentioning
confidence: 99%